The prevalence of measles vaccination in measles-infected healthcare workers: A systematic review and meta-analysis - Sujata Saha; Sumanta Saha (Journal of Infection Prevention, 2026)
Aims Documentable evidence of previous receipt of 2-dose of measles-containing vaccine (MCV) is often sufficient as proof of measles immunity in healthcare workers (HCWs). The usefulness of this policy was assessed by estimating the global prevalences of different MCV-receipt statuses in measles infected HCWs. Methods Eligible publications since 1974 were searched in PubMed, Embase, and Scopus databases. Pooled prevalences were estimated by prevalence meta-analysis and meta-regressed using durations since MCV inclusion in the national immunization schedule (NIS) of respective study countries to measles outbreak years as a moderator. Results Of the 7571 citations retrieved, 27 studies reporting on 1319 measles-infected HCWs aged 18-60 years (outbreak years: 1985–2019) were reviewed. Prevalences of measles-infected HCWs were– a. by MCV-receipt statuses: ≥1-dose: 41.0% (95% CI: 28.0, 55.0); ≥2-dose: 28.0% (95% CI: 11.0, 46.0); unvaccinated: 31.0% (95% CI: 17.0, 46.0); unknown: 21.0%; b. by gender: females: 65.0% (95% CI: 57.0, 72.0); males: 35.0% (95% CI: 28.0, 43.0); c. by birth year: born after MCV inclusion in NIS: 77.0% (95% CI: 66.0, 87.0) and in born before: 6.0% (95% CI: 0.0, 17.0); d. by health profession: nurses: 31.0% (95% CI: 24.0, 39.0); doctors: 27.0% (95% CI: 19.0, 36.0); students 5.0% (95% CI: 1.0, 12.0). The measles risk in ≥2-dose of MCV recipient HCWs increased with duration since MCV inclusion in NIS to outbreak occurrences (p < .05). Conclusion In measles infected HCWs, as the rates of being ≥2-dose MCV recipient or unvaccinated were substantial and comparable, the role of documented 2-dose of MCV receipt alone as a proof of measles immunity remains uncertain.